Effects of powder recycling on laser-based powder bed fusion produced SS316L parts - Gopaluni Aditya; Nayak Chinmayee; Piiroinen Aki; Kantonen Tuomas; Salminen Antti (United Kingdom, 2025)
Laser-based powder bed fusion (PBF-LB/M) is one of the extensively used additive manufacturing (AM) methods as the parts printed by PBF-LB/M have high resolution due to low layer thickness. Recycling and Reusing of the powder in this process has a significant impact on the surface roughness, mechanical properties such as hardness, elastic modulus and fracture strength etc. of the manufactured parts. The aim of the present study is to understand the effects of powder recycling on the properties of SS316L parts such as hardness and surface roughness. The developed method featured the use of SS316L powder five times over with weight percentage adjusted as required for the build job. The printed parts were checked for surface roughness across different surfaces with respect to the build direction along with Vickers hardness test. The surface roughness of the parts before polishing showed a steady increasing trend of about 40% with the recycling count while there was no significant effect on hardness as the values stayed in the range of 230+/-5 HV. Powder morphology studies with SEM displayed visible changes in terms of satellite formations, broken particles etc. with the increase in counts of recycling and particle size distribution showed a linear increase with the increase in recycling counts. This study was performed within the limited scope of a bigger study for which a detailed methodology of powder recycling will be developed.
NOLAMP- Nordic Laser Materials Processing Conference (19TH-NOLAMP-2023) 22/08/2023 - 24/08/2023 Turku, Finland